2018
DOI: 10.3233/nre-172380
|View full text |Cite
|
Sign up to set email alerts
|

An international perspective on educators’ perceptions of children with Traumatic Brain Injury

Abstract: BACKGROUND: Educators lack understanding of traumatic brain injury (TBI), which can

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…ough TBI is thought to a ect approximately 8-12 per cent of the population, it is not routinely assessed and recognized by the education system, with children misinterpreted as 'di cult'. It is of no surprise that children are therefore struggling to adequately and fairly access education, limiting future prospects (Silver et al, 2001;Frost et al, 2013;Kahn et al, 2018).…”
Section: Poverty and Educationmentioning
confidence: 99%
“…ough TBI is thought to a ect approximately 8-12 per cent of the population, it is not routinely assessed and recognized by the education system, with children misinterpreted as 'di cult'. It is of no surprise that children are therefore struggling to adequately and fairly access education, limiting future prospects (Silver et al, 2001;Frost et al, 2013;Kahn et al, 2018).…”
Section: Poverty and Educationmentioning
confidence: 99%
“…However, approximately 10-15% of mild injuries are thought to lead to long-term deficits [10]. Research has shown that potential serious consequences of concussion and brain injury are poorly understood by members of the public, educators and healthcare professionals [11][12][13].…”
Section: Special Issue: Childhood Acquired Brain Injury Affects Adult Outcomesmentioning
confidence: 99%
“…In a systematic review of clinician and educator experiences of facilitating the return‐to‐school (Hartman, Duncanson, et al, 2015), school‐based educators' perspectives were largely represented in combination with the perspectives of other professionals. Educators' understanding of the educational needs of child with an ABI has been investigated in two recent studies: an international study of educator perspectives on children with traumatic brain injury (Kahn et al, 2018) and a UK‐based study which analysed the ABI knowledge of Special Education Needs Coordinators (SENCOs) via a survey (Howe and Ball, 2017). Neither of them focused specifically on the return‐to‐school; however, both studies identified a lack of training on educating children with an ABI.…”
Section: Introductionmentioning
confidence: 99%